2009
DOI: 10.2166/wst.2009.520
|View full text |Cite
|
Sign up to set email alerts
|

A case independent approach on the impact of climate change effects on combined sewer system performance

Abstract: Design and construction of urban drainage systems has to be done in a predictive way, as the average lifespan of such investments is several decades. The design engineer has to predict many influencing factors and scenarios for future development of a system (e.g. change in land use, population, water consumption and infiltration measures). Furthermore, climate change can cause increased rain intensities which leads to an additional impact on drainage systems. In this paper we compare the behaviour of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 13 publications
0
33
0
1
Order By: Relevance
“…In May 2007 a new substrate system was implemented on the central portion of this green roof, with an extension of about 350 m 2 and an average total depth of about 40 cm (see Figure 2). The new solution consists of a protection layer (300 gr/m 2 geotextile), a drainage layer (implemented by lapillus for a depth of 20 cm), a filter layer (100 gr/m 2 geotextile) and a growing medium with mixed soil (lapillus, pumice, zeolite and 200 l/m lapillus and 30% pumice while in the other half the blend is 70% lapillus, 20% pumice and 10% zeolite.…”
Section: The Full Scale Experimental Sitementioning
confidence: 99%
See 1 more Smart Citation
“…In May 2007 a new substrate system was implemented on the central portion of this green roof, with an extension of about 350 m 2 and an average total depth of about 40 cm (see Figure 2). The new solution consists of a protection layer (300 gr/m 2 geotextile), a drainage layer (implemented by lapillus for a depth of 20 cm), a filter layer (100 gr/m 2 geotextile) and a growing medium with mixed soil (lapillus, pumice, zeolite and 200 l/m lapillus and 30% pumice while in the other half the blend is 70% lapillus, 20% pumice and 10% zeolite.…”
Section: The Full Scale Experimental Sitementioning
confidence: 99%
“…Kleidorfer et al [2] analyzed e.g. the impact of urbanization, expressed by the increase of impervious area, in conjunction with possible global warming scenarios on urban hydrology and in particular on the efficiency of a combined sewer system.…”
Section: Introductionmentioning
confidence: 99%
“…The above evaluation models have played an important role in the vulnerability analysis of water distribution systems, but there were a few studies for urban drainage systems [2,[32][33][34][35][36][37][38]. For example, Moderl et al (2009) developed the VulNetUD method, which is for GIS-based identification of vulnerable sites of urban drainage systems using hydrodynamic simulations undertaken using EPA SWMM [32].…”
Section: Introductionmentioning
confidence: 99%
“…However, few vulnerability assessment studies investigate the vulnerability of the entire drainage systems [41], especially the comparative analysis of the vulnerability for pipe networks which have different layouts, such as tree and loop drainage systems. Though loop drainage systems are not common, there are still many loop networks in reality [34,36,[42][43][44]. For example, Yongwon et al (2015) stated that "loops are easily found in urban catchments not just for water supply pipe networks, but also for stormwater drainage pipe networks" [42], and investigated the behavior of a fully looped network for a given rainfall event using the Storm Water Management Model.…”
Section: Introductionmentioning
confidence: 99%
“…Kleidorfer et al, 2009), the new approach proposed in this paper considers the temporal dynamics of adaptation strategies.…”
Section: Introductionmentioning
confidence: 99%